The Image of the New Adam in the Book of Daniel (Daniel 4 and 7) - Igor Bessonov (Old Testament Essays)
The interpretation of the Son of Man figure in Dan 7 is one of the most hotly debated issues in biblical scholarship. This article is based on the premise that the analysis of the Aramaic Daniel (Dan 1-7), the earlier part of the modern Hebrew-Aramaic book of Daniel, could enable us to determine the original interpretation of the Son of Man figure. A comparison of Dan 7 and Dan 4 allows us to conclude that in the Aramaic Daniel there is a consistent analogy between Adam, Nebuchadnezzar and the Son of Man. Therefore, the Son of Man figure may be defined as the "new Adam" if we use a later vocabulary. In the interpretation of the prophetic dream vision, this figure turns out to symbolise the nation of Israel, which is part of the tendency to identify Israel with man as such and attribute Adam's heritage to Israel.